Edible Nuts for Memory - Arslan, Jamshed; Gilani, Anwar-ul-Hassan; Jamshed, Humaira; Khan, Sumaiya F.; Kamal, Mohammad A. (Current Pharmaceutical Design, 2020)
Nuts hold prime significance throughout the world as they offer multiple health benefits owing to their highly nutritious profile. A number of scientific studies have demonstrated their actions against inflammation, oxidative damage, the aging process, as well as dementia or memory loss. However, only walnuts, followed by almonds, hazelnuts and pistachios, have shown promising results in empirical studies for memory improvements. So, the current review focuses on presenting hypotheses regarding anti-dementia property of nine different nuts: almond, walnut, pistachio, Brazil nut, peanut, pecans, cashew, hazelnut, and chestnut. The nutritious profile of nuts contains essential fats (mostly mono- and poly-unsaturated fatty acids), proteins (source for arginine, lysine and tryptophan), vitamins (riboflavin, folate, and various tocopherols), fibers, minerals (calcium, sodium, magnesium, phosphorus and potassium) and trace elements (copper, zinc, and selenium). Interestingly, the constituents of natural products, nuts being an excellent example, work synergistically and/or in a side-effect neutralizing manner. These latter properties can make nuts an alternate therapy for humankind to fight against memory loss.
Keywords: pistachio